La enfermedad holandesa: Su inicio y desarrollo en Colombia (2016)
The following work is the compilation of different studies done on the Dutch Disease, studied from its origin in Holland to its arrival to Colombia. In general terms, it describes the principle characteristics of the Dutch Disease, its origin and development in the social, economic and political environment and the subsequent consequences of it. At the end, this work exposes the political measurements that permit the control of the positive effects of the booms in the economy and the possibility to handle them in a better way to face the crisis periods and the serious political and social consequences.